Hexactinellid Cave, a unique deep-sea habitat in the scuba zone - Vacelet, J.; Boury-Esnault, N.; Harmelin, J.-G. (Deep Sea Research I, 1994)
Deep-sea organisms have colonized an unusual Mediterranean cave 18-24 m below the sea surface, in which the entrapment of a cold water mass results in stable temperature conditions throughout the year. These conditions, together with lack of light and limited food resources approximate those of the deep Mediterranean. Among other deep-sea organisms. Oopsacas minuta, a representative of the bathyo-abyssal cold-water-adapted hexactincllid sponges, reproduces here year round, making possible the first observations of larval behavior and ultrastructure on this phylogenetically important group of invertebrates. Easily accessible to scuba divers, this "bathyal island" in the littoral zone offers exceptional opportunities for deep-sea biology